Studi Penggunaan Counterweight sebagai Penanggulangan Longsor pada Lereng Disposal di Pit 302 PT Jembayan Muarabara Kecamatan Marangkayu Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Tommy Aria Pradana; Tommy Trides; Windhu Nugroho; Revia Oktaviani; Albertus Juvensius Pontus; Ardhan Ismail; Rety Winonazada (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Disposal area is an area at an open pit mine that is used as a place to store or dispose of worthless materials. Disposal must also follow the specified safety factor standards, if the disposal design is not safe after being analyzed by a geotechnical engineer, the design must be redesigned to achieve the desired safety factor value. One way to increase the fk value is to make a Counterweight plan in making disposal. Where Counterweight is a fill material that is made with special treatment so that the soil bearing capacity increases which functions to withstand the load on it. Landslides on disposal slopes are one of the serious problems faced in mining activities, especially in areas with vulnerable geological and topographic conditions. PT Jembayan Muarabara, which operates in Marangkayu District, Kutai Kartanegara Regency, East Kalimantan Province, is no exception to this challenge. The A–A’ cross section shows a safety factor value of 1.118 in saturated conditions, which indicates that the slope is at a stable limit and needs to be improved through engineering such as adding counterweights. The B–B’ cross-section has a safety factor value of 2.332, which is included in the safe category and has met the provisions of the ESDM Ministerial Decree No. 1827 K/30/MEM/2018. The C-C’ cross-section has a safety factor value of 1.511, which is included in the safe category and has met the provisions of the ESDM Ministerial Decree No. 1827 K/30/MEM/2018.